PSXV-35 Impacts of bovine maternal nutrition on muscle fiber type in skeletal muscle of the progeny. (7th December 2018) - Ineck, N; Thornton, K; Christensen, R; Rood, K; Carpenter, C; Legako, J; Quarnberg, S
Abstract: We investigated how nutritional restriction of cows during the second trimester of gestation impacted the muscle fiber type proportions of offspring at 10 months after birth. Cows were bred by the same sire, stratified by body weight (P = 0.80) and body condition score (BCS) (P = 0.72), and allocated to one of two treatment groups during the second trimester of gestation: maintenance (n = 16, 2309 kg/ha dry matter (DM)) or restricted (n = 18, 1662 kg/ha DM). Restricted cows had a BCS 1.55 lower (P = 0.001) than maintenance cows at the end of the period and a weight difference of 188 kg (P = 0.024). After the second trimester, all cows were fed similarly and there was no difference (P > 0.80) in body weight or BCS between the dams from either treatment at the end of the third trimester. There were no differences (P > 0.05) in body weight of offspring at birth, throughout growth, or during the feedlot. Skeletal muscle biopsies were collected from the biceps femoris of offspring at 10 months of age and stained using both a succinate dehydrogenase stain and myosin adenosine triphosphate, There were no differences (P > 0.15) in proportions of type I, IIa or IIb fibers when comparing offspring from maintenance or restricted dams. However, the proportion of type I fibers was negatively correlated (r = -0.48, P = 0.06) with Warner-Bratzler shear force value and type IIa fiber proportions showed a weak, positive correlation (r = 0.37, P = 0.10) with total DM intake of the offspring during the feedlot phase. These preliminary data demonstrate that a nutritional restriction during the second trimester of gestation does not significantly alter fiber type proportions of the offspring prior to entering the feedlot.